Health care for women in situations of violence: discoordination of network professionals - Jaqueline Arboit; Stela Maris de Mello Padoin; Letícia Becker Vieira; Cristiane Cardoso de Paula; Marta Cocco da Costa; Laura Ferreira Cortes
Abstract OBJECTIVE To learn the conceptions and actions of health professionals on the care network for women in situations of violence. METHOD A qualitative, descriptive, exploratory study was conducted between April and July 2015 with the participation of 21 health professionals from four primary health care teams in a city of the central region of the state of Rio Grande do Sul. Data were collected by means of individual semi-structured interviews. Content analysis was used for data systematization. RESULTS Health professionals recognized the importance of the health care network for coping with the problem of violence against women. However, their conceptions and actions were limited by the discoordination or absence of integration among professionals and services of the care network. CONCLUSION The conceptions and actions of health professionals contribute to the discoordination among the services. It is necessary to reflect on the daily practices of care for women in situations of violence.